Signaling Green: Impact of Green Product Attributes on Consumers Trust and the Mediating Role of Green Marketing - Khan, Kashif Ullah; Atlas, Fouzia; Arshad, Muhammad Zulqarnain; Akhtar, Sadia; Khan, Farhan (Frontiers in Psychology, 2022)
The purpose of this research is to highlight the relationship between green product attributes and consumer trust that influence consumers’ decision to purchase green products in the context of Pakistan. This paper contributes to determining quantitatively how green product attributes such as physical, perceptual, and reflexive attributes influence consumer trust to purchase a green product and investigates the mediating role of green marketing. Data was collected from different industrial sectors through a survey questionnaire. We employed Structural Equation Modeling (SEM) using SMART-PLS software to check the reliability, the validity of the constructs, and to test the hypotheses. This study reveals variations in terms of shaping the sustainable consumers buying behavior by modifying product attributes and green marketing strategies which are in congruence with the proposed hypotheses of this study. In the end, the findings and interpretations of the results are given which can guide the managers to develop effective green marketing campaigns in reshaping the purchase intentions of consumers towards their green products.